2002
DOI: 10.1124/jpet.302.1.111
|View full text |Cite
|
Sign up to set email alerts
|

A Novel cAMP-Stimulated Pathway in Protein Phosphatase 2A Activation

Abstract: Elevated cAMP in NRK-52E and L6 cells causes a marked reduction in the phosphorylation of numerous phosphoproteins, as detected initially with phosphoserine-specific antibodies. Here, we show that elevation of cAMP in NRK cells by forskolin/3-isobutyl-1-methylxanthine (IBMX) treatment decreased phosphorylation of substrates for different protein kinases, pointing to a common protein phosphatase as a target for cAMP-dependent regulation. Forskolin/IBMX treatment completely dephosphorylated a selective protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 39 publications
3
71
1
Order By: Relevance
“…Restoration of PP2A activity impairs BCR/ABL leukaemogenesis: therapeutic effects of the PP2A activator forskolin Consistent with the negative effects of PP2A on BCR/ABL expression and function, restoration of PP2A activity back to normal levels via SET downregulation, PP2Ac overexpression or treatment with the potent PP2A activator forskolin (Feschenko et al, 2002) or with 1,9-dideoxy-forskolin (forskolin derivative that lacks adenylate cyclase-cAMP- (Seamon and Daly, 1981) activating function) induces marked apoptosis, reduces proliferation, impairs colony formation, inhibits tumorigenesis and restores differentiation of patient-derived myeloid CML-BC CD34 þ cells and/or BCR/ ABL-transformed cell lines, regardless of their degree of sensitivity to imatinib . Notably, the imatinib-, AMN107-and dasatinib-resistant T315I BCR/ABL þ cells are also sensitive to PP2A activation .…”
Section: Adverse Molecular Effects Of Bcr/abl and Pp2amentioning
confidence: 85%
See 2 more Smart Citations
“…Restoration of PP2A activity impairs BCR/ABL leukaemogenesis: therapeutic effects of the PP2A activator forskolin Consistent with the negative effects of PP2A on BCR/ABL expression and function, restoration of PP2A activity back to normal levels via SET downregulation, PP2Ac overexpression or treatment with the potent PP2A activator forskolin (Feschenko et al, 2002) or with 1,9-dideoxy-forskolin (forskolin derivative that lacks adenylate cyclase-cAMP- (Seamon and Daly, 1981) activating function) induces marked apoptosis, reduces proliferation, impairs colony formation, inhibits tumorigenesis and restores differentiation of patient-derived myeloid CML-BC CD34 þ cells and/or BCR/ ABL-transformed cell lines, regardless of their degree of sensitivity to imatinib . Notably, the imatinib-, AMN107-and dasatinib-resistant T315I BCR/ABL þ cells are also sensitive to PP2A activation .…”
Section: Adverse Molecular Effects Of Bcr/abl and Pp2amentioning
confidence: 85%
“…forskolin; Feschenko et al, 2002) or by interfering with the SET/PP2A interplay (i.e. PP2Ac overexpression, SET knockdown), promotes BCR/ABL tyrosine dephosphorylation (inactivation) which, in turn, trigger its proteasome-dependent degradation .…”
Section: Adverse Molecular Effects Of Bcr/abl and Pp2amentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphatase that specifically dephosphorylates p38 MAPK-␥ has not yet been identified. However, cAMP-PKA signals are reported to enhance activity of protein phosphatase (PP)2A (Feschenko et al, 2002). PP2C is also known as cAMP-coupled phosphatase (Yokoyama et al, 1995), and PP1 and PP5 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms by which FSH itself limits excessive cAMP catabolism by reversing phosphorylation of particulate PDE4 activities are still unknown. Previous studies have shown that cAMP transiently up-or down-regulates PP2A activity in various cell types (Feschenko et al 2002, Moon & Lerner 2003, Pullar et al 2006, but the regulatory mechanisms controlling PP2A activity are not fully understood. In Sertoli cells, increase in PP2A activities under FSH conditions does not result from transcriptional up-regulation of PP2A-C isoforms, in agreement with the autoregulatory mechanism preventing fluctuation in PP2A-C translation (Baharians & Schonthal 1998).…”
Section: Discussionmentioning
confidence: 99%